TEACHERS AND STUDENTS' PERCEPTIONS OF ONLINE NATURAL SCIENCE LEARNING - Fitri Yenti; Rahmadhani Fitri (Universitas Negeri Padang, 2022)
The Corona Virus Disease (COVID-19) pandemic has a profound effect on education today. As a result, personal academic activities including laboratory practice in learning should be avoided. Social distancing makes several schools, colleges and companies closed and applies online learning. Online learning is a form of education where a lot of media will be adopted for the learning and intercommunication system between students and teachers. One of the strategies used for learning is to take advantage of existing technology. This study aims to determine the perceptions of teachers and students towards online learning during the pandemic. The research method was carried out quantitatively by interviewing and distributing questionnaires containing statement items with five aspects of the focus of the study, namely implementation, interest, motivation, attitudes and responses and student satisfaction during online learning. Quantitative data analysis was carried out using a Likert scale survey method with 1 biology teacher and 103 students, namely students of class X, XI and XII IPA MAN 1 Padang Panjang as the research sample. The results showed that the five aspects of learning related to teacher and student perceptions of online learning during the pandemic had positive results. The researcher's findings are positive, it does not mean that there are no obstacles in the implementation of online biology learning such as difficult places to access the internet, internet quotas and the material and assignments given are difficult for students to understand.